2001
DOI: 10.1155/s1357714x01000196
|View full text |Cite
|
Sign up to set email alerts
|

Intraosseous Schwannoma (Neurilemmoma) of the Cervical Spine

Abstract: Purpose: To report on an extremely rare tumour located in the cervical spine, its treatment and result. Review of the literature. Patient: Case report of a 38-year-old woman with an intraosseous schwannoma of the cervical spine. Results: After local curettage no evidence for local recurrence at long-term follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…Type VII, which has foraminal or intraspinal extension, can present with radicular pain or myelopathic features. Type VIII, which has an exophytic component, may present with symptoms related to compression of the surrounding structures such as dysphagia, stridor or pain, as noted in the present case [7]. Inaoka et al [10] and Barnowsky and Dalai [11] have described paravertebral schwannomas with an aggressive vertebral extension.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Type VII, which has foraminal or intraspinal extension, can present with radicular pain or myelopathic features. Type VIII, which has an exophytic component, may present with symptoms related to compression of the surrounding structures such as dysphagia, stridor or pain, as noted in the present case [7]. Inaoka et al [10] and Barnowsky and Dalai [11] have described paravertebral schwannomas with an aggressive vertebral extension.…”
Section: Discussionmentioning
confidence: 68%
“…In view of the peculiar exophytic growth pattern seen in the present case, we suspect the second mechanism mentioned above as the possible mode of occurrence. Such a pattern of growth has been reported only twice in the literature [7,8]. …”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Schwannoma is a very slow-growing mass and often is asymptomatic. 2,3,5,9 However, symptoms may occur as a result of nerve compression caused by the growth of the tumor. It has been reported that schwannoma presents as a palpable mass with local pain and paraesthesia, which is exacerbated by direct percussion of the mass.…”
Section: Discussionmentioning
confidence: 99%
“…7,10 Although schwannoma may occur at any age, it is commonly seen between the ages of 20 and 50 years, with equal male and female predisposition and no racial predilection. 2,3,7,9,11 Most lesions are usually solitary unless they are associated with neurofibromatosis, which is often multiple. 12 Unlike neurofibromas, which are highly associated with von Recklinghausen disease, schwannoma rarely has a malignant potential.…”
Section: Discussionmentioning
confidence: 99%